Assessment of Cytocompatibility and Magnetic Properties of Nanostructured Silicon Loaded with Superparamagnetic Iron Oxide Nanoparticles. (18th February 2015) - Granitzer, Petra; Rumpf, Klemens; Tian, Yuan; Coffer, Jeffery; Akkaraju, Giri; Poelt, Peter; Reissner, Michael
Abstract : The aim of this work is to create a biocompatible superparamagnetic nanocomposite applicable as vehicle for magnetically guided drug delivery. Both materials, the nanostructured silicon as well as the iron oxide nanoparticles offer low toxicity. Therefore Fe3 O4 -nanoparticles have been incorporated within nanostructured silicon. On the one hand the iron oxide nanoparticles have been synthesized in solution and then infiltrated and on the other hand they have been chemically grown within the pores. The magnetic properties of the system have been optimized concerning the blocking temperature TB and the magnetic moment M, which are conflicting parameters. A particle-size/distance and template dependent assessment of the magnetic properties of the nanocomposite will be presented. Although the growth of iron oxide particles within the porous template is not easy to control the blocking temperature of the composite could be achieved far below room temperature.